2018
DOI: 10.1111/jbi.13489
|View full text |Cite
|
Sign up to set email alerts
|

Functional and phylogenetic diversity of bird assemblages are filtered by different biotic factors on tropical mountains

Abstract: Aim It is not yet clear whether similar mechanisms influence the assembly of ecological communities across different continents. Here, we investigated the functional and phylogenetic diversity of bird assemblages along elevational gradients in two biogeographic regions in order to identify how these are driven by biotic factors, such as food resources and vegetation structure, and abiotic factors, such as ambient temperature and precipitation. Location Two 2,000‐m elevational gradients in the Ecuadorian Andes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
74
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 96 publications
9
74
5
2
Order By: Relevance
“…Of course, change in abiotic factors across elevations may reflect indirect effects beyond physiological constraints, such as the availability of food (Ferger, Schleuning, Hemp, Howell, & Böhning-Gaese, 2014;Hanz et al, 2019;Janzen, 1973), given that adults of most species do not appear to be physiologically limited by temperature (Londoño et al, 2017). Indeed, the existence of elevational reversals in some pairs of Andean birds (Remsen & Cardiff, 1990;Remsen & Graves, 1995) also makes it unlikely that direct effects of abiotic factors are the primary limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, change in abiotic factors across elevations may reflect indirect effects beyond physiological constraints, such as the availability of food (Ferger, Schleuning, Hemp, Howell, & Böhning-Gaese, 2014;Hanz et al, 2019;Janzen, 1973), given that adults of most species do not appear to be physiologically limited by temperature (Londoño et al, 2017). Indeed, the existence of elevational reversals in some pairs of Andean birds (Remsen & Cardiff, 1990;Remsen & Graves, 1995) also makes it unlikely that direct effects of abiotic factors are the primary limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Kilimanjaro. Hanz et al () reported that avian functional diversity increased with increasing resource availability, whereas phylogenetic diversity increased with increasing heterogeneity of vegetations and canopy closure along elevational gradients in Ecuador and Tanzania. However, to our knowledge, our study is the first to bring information about the role of detailed forest parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental gradients allow separation of stochastic from deterministic drivers of ecological communities Condit et al, 2002;Jankowski, Ciecka, Meyer, & Rabenold, 2009;Jankowski et al, 2012;Legendre, Borcard, & Peres-Neto, 2005;Swenson et al, 2011;Whittaker, 1960). In particular, latitudinal and elevational gradients, along which temperature, precipitation and possibly productivity vary, have been studied intensively to help identify the extent to which different biotic and abiotic variables determine community composition (Hanz et al, 2019;Jankowski et al, 2009Jankowski et al, , 2012Kraft et al, 2011;Qian & Ricklefs, 2007;Rodríguez & Arita, 2004;Swenson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The harsh versus benign environment dichotomy that gave rise to the BI hypothesis is present in dry versus wet lowland tropical forests, yet this hypothesis remains largely untested in Neotropical bird communities (but see Hanz et al, 2019 for an analysis of bird community turnover along a temperature and precipitation gradient). Analogous to latitudinal and elevational temperature gradients, climatic harshness usually increases as precipitation decreases (when controlling for temperature), and the potential for biotic interactions (intra-and inter-trophic) increases as precipitation increases.…”
Section: Introductionmentioning
confidence: 99%